'Feeling fat, ' eating pathology, and eating pathology-related impairment in young men and women. Issue 5 (3rd September 2021) - Mehak, Adrienne; Racine, Sarah E.
ABSTRACT: ' Feeling fat' has received little empirical attention despite clinical recognition as an eating disorder maintenance factor. This experience also occurs in non-clinical populations and may relate to elements of subclinical eating pathology. The present study examined whether 'feeling fat' independently contributes to eating pathology and eating pathology-related impairment, over and above over-evaluation of weight and shape and dysphoria. University students ( N = 990; 54.3% female) completed questionnaires measuring these constructs. Moderated multiple hierarchical regression analyses evaluated 'feeling fat''s unique contribution to eating pathology and impairment, and the moderating effects of gender and eating disorder symptom severity. 'Feeling fat' accounted for significant unique variance in eating pathology, but not eating pathology-related impairment, over and above over-evaluation of weight and shape and dysphoria. The relationship between 'feeling fat' and eating pathology-related impairment was stronger in women than in men. Symptom severity did not moderate the relationship between 'feeling fat' and either dependent variable. 'Feeling fat' distinctly relates to eating pathology in a sample of young adults, suggesting that 'feeling fat' deserves attention in individuals without eating disorders. Future research should longitudinally investigate the direction of the relationship between 'feeling fat' and eating pathology and examine mechanisms of gender differences in 'feeling fat.'